Older Adults’ Emotion Recognition Ability Is Unaffected by Stereotype Threat - Atkinson, Lianne; Murray, Janice E.; Halberstadt, Jamin (Frontiers in Psychology, 2021)
Eliciting negative stereotypes about aging commonly results in worse performance on many physical, memory, and cognitive tasks in adults aged over 65. The current studies explored the potential effect of this ‘stereotype threat’ phenomenon on older adults’ emotion recognition, a cognitive ability that has been demonstrated to decline with age. In Study 1, stereotypes about emotion recognition ability across the lifespan were established. In Study 2, these stereotypes were utilised in a stereotype threat manipulation that framed an emotion recognition task as assessing either cognitive ability (stereotypically believed to worsen with age), social ability (believed to be stable across lifespan), or general abilities (control). Participants then completed an emotion recognition task in which they labelled dynamic expressions of negative and positive emotions. Self-reported threat concerns were also measured. Framing an emotion recognition task as assessing cognitive ability significantly heightened older adults’ (but not younger adults’) reports of stereotype threat concerns. Despite this, older adults’ emotion recognition performance was unaffected. Unlike other cognitive abilities, recognising facially-expressed emotions may be unaffected by stereotype threat, possibly because emotion recognition is automatic, making it less susceptible to the cognitive load that stereotype threat produces.